(untitled) (Dermatology Reports, 2022)
Lupus panniculitis is included in the chronic cutaneous lupus erythematosus group. An 18-year-old female patient came with the complaint of lumps on her face. When she was 16 years old, the patient started to complain about lumps on her right lower arm. Lumps were observed on her left cheek and right chin during the ongoing treatment. Histopathology results showed lymphocyte infiltration in between lobular adipocyte with fibrotic and fat necrosis in the subcutis. Lupus panniculitis lesions in this patient were found both on her face and on her lower arms, which are not considered common predilection sites of lupus panniculitis. The skin lesion observed in this patient was also bilateral and symmetrical, which was a rare finding.